Nuclear extrusion precedes discharge of genomic DNA fibers during tunicamycin‐induced neutrophil extracellular trap‐osis (NETosis)‐like cell death in cultured human leukemia cells. (4th March 2016) - Nakayama, Tomofumi; Saitoh, Noriko; Morotomi‐Yano, Keiko; Yano, Ken‐ichi; Nakao, Mitsuyoshi; Saitoh, Hisato
Abstract: We previously reported that the nucleoside antibiotic tunicamycin (TN), a protein glycosylation inhibitor triggering unfolded protein response (UPR), induced neutrophil extracellular trap‐osis (NETosis)‐like cellular suicide and, thus, discharged genomic DNA fibers to extracellular spaces in a range of human myeloid cell lines under serum‐free conditions. In this study, we further evaluated the effect of TN on human promyelocytic leukemia HL‐60 cells using time‐lapse microscopy. Our assay revealed a previously unappreciated early event induced by TN‐exposure, in which, at 30–60 min after TN addition, the cells extruded their nuclei into the extracellular space, followed by discharge of DNA fibers to form NET‐like structures. Intriguingly, neither nuclear extrusion nor DNA discharge was observed when cells were exposed to inducers of UPR, such as brefeldin A, thapsigargin, or dithiothreitol. Our findings revealed novel nuclear dynamics during TN‐induced NETosis‐like cellular suicide in HL‐60 cells and suggested that the toxicological effect of TN on nuclear extrusion and DNA discharge was not a simple UPR.